A new way to define better improvement options of existing buildings for energy saving. Issue 9 (20th October 2016) - Barkhudaryan, Naira R.; Roshan, Gholamreza; Orosa, José A.
Abstract : This work proposes a new methodology that is based on the ISO 13790 standard and the Monte Carlo method, which helps obtain the probability density function of the energy consumption in real buildings. The energy consumption under different improvement processes for each building was modelled considering variables such as thermal inertia, number of air changes and number of occupants. Some types of modifications, which are common and basic, were found to exert a clear effect over building energy consumption but these were not exactly defined by recommendations of most of the standards. Its effect was mostly due to the two parameters – the number of occupants and the number of air changes. These results should be considered in future during development of new standards for the purpose of defining the optimal amount of building energy consumption.